Not all secondary bone tumours are secondaries. Concurrent metastatic breast carcinoma and chondrosarcoma of the femur. (9th April 2015) - Nath, Preethy; Sankey, Elizabeth; Murray, Elisabeth; Kurup, Harish
Abstract : We present a case of metastatic adenocarcinoma of the breast in a patient who sustained a pathological fracture of the distal femur. Histology of the distal femur lesion excised at the time of endoprosthetic replacement confirmed this to be a primary chondrosarcoma. We have reviewed the literature and identified previously documented cases of concurrent breast carcinoma and chondrosarcoma of bone. A high index of suspicion is warranted and the diagnosis must be first confirmed before rushing to internal fixation (therapeutic or prophylactic) assuming them to be secondary bone lesions from the known primary cancer even in patients with multiple metastases.